2003
DOI: 10.1007/s10350-004-6684-0
|View full text |Cite
|
Sign up to set email alerts
|

Management and Treatment Outcome of Pouch-Vaginal Fistulas Following Restorative Proctocolectomy

Abstract: Pouch-vaginal fistulas are a difficult problem in females following restorative proctocolectomy. However, local repair can be successful with good functional outcomes. Redo restorative proctocolectomy may also achieve healing if local repairs are not possible or have failed. A delayed diagnosis of Crohn's disease results in worse treatment outcome and higher pouch failure rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
73
1
7

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(81 citation statements)
references
References 27 publications
0
73
1
7
Order By: Relevance
“…The majority of studies have reported that pouchitis is the most frequent long-term complication of the IPAA, ranging from 12% to 50% (18,19). Pouch-vaginal fistula has been reported as a major complication in women undergoing IPAA, of which the incidence ranges from 3.3%-12% (20)(21)(22). Small bowel obstruction following IPAA varies between 12-24% (23).…”
Section: Discussionmentioning
confidence: 99%
“…The majority of studies have reported that pouchitis is the most frequent long-term complication of the IPAA, ranging from 12% to 50% (18,19). Pouch-vaginal fistula has been reported as a major complication in women undergoing IPAA, of which the incidence ranges from 3.3%-12% (20)(21)(22). Small bowel obstruction following IPAA varies between 12-24% (23).…”
Section: Discussionmentioning
confidence: 99%
“…Structural or OO dysfunctions have better results compared with septic complications. 7,11,12,17,28 Thus, it is important to distinguish between these entities and to know the aetiology of pouch malfunctions in order to choose the optimal treatment. The commonest conditions of surgical interest are discussed below; medical conditions and conservative management will also be briefly addressed.…”
Section: Discussionmentioning
confidence: 99%
“…15 Pouch retention rates after reconstructive surgery range between 0 and 50%. 12,[17][18][19][20][21][22][23][24][25][26][27] Indications for pouch salvage surgery affect the outcomes. For this reason, we propose a classification of reasons for pouch salvage in Table 4.…”
Section: Discussionmentioning
confidence: 99%
“…Detailed information on salvage using abdominal pouch advancement is lacking 2,3 . Experience with this approach is reported.…”
Section: Introductionmentioning
confidence: 99%